Effect of Music Therapy On Pain Perception, Fatigue Level, And Physiological Variables in Patients Undergoing Hemodialysis- A Prospective Randomized Interventional Trial: Life Sciences-Nursing - .R, Sobana; K, jaiganesh; S, Parthasarathy (International Journal of Life Science and Pharma Research, 2023)
Chronic renal failure (CRF) is a severe and chronic illness that can significantly impact a person’s quality of life. It is caused by various pathologies and can lead to multiple complications, including fatigue and chronic pain. Hemodialysis is a standard and lifesaving treatment for patients with CRF, but the prolonged immobilization required during this procedure can exacerbate fatigue and pain. Music therapy is a non-invasive treatment that has positively impacted patients undergoing hemodialysis. In the study we have done, the therapy consisted of passive listening and active participation in the form of deep breathing for eight weeks. To provide music therapy based on client preference to patients undergoing hemodialysis for chronic renal failure. To observe the fatigue and subjective pain perception level after eight weeks of musical intervention.The sessions began with a warm-up session of OM chanting, which was used to set the atmosphere and bring attention to the subject. Then, devotional songs were played for 10 minutes based on the patient’s preferences, followed by 20 minutes of Indian classical Veena music. The therapy sessions were administered every third day, twice a week when the patients underwent hemodialysis. Each session lasted around 3 hours. Subjective parameters of fatigue and pain perception were assessed before the intervention, after four weeks, and after eight weeks of musical intervention. The results indicated that music therapy lowered these patients’ fatigue and pain perception. The fatigue level, estimated by the CIS (Checklist Individual Strength) score, was reduced by 30%, and the pain perception score dropped from 8 to 6.5. The findings of this study suggest that music therapy can be an effective complementary treatment for patients undergoing hemodialysis, as it can help to reduce fatigue and pain perception. It is essential because these symptoms can significantly impact patients’ quality of life and may impact adherence to treatment regimens. However, it’s also worth noting that this study only assesses the effect in a small sample size. For a short period, more research is needed in a larger population with a longer duration. Exploring different music or other therapeutic techniques is also beneficial to find the most effective approach for individual patients.